2020
DOI: 10.1111/eea.12869
|View full text |Cite
|
Sign up to set email alerts
|

Differential induction of volatiles in rice plants by two stink bug species influence behaviour of conspecifics and their natural enemy Telenomus podisi

Abstract: Tritrophic interactions mediated by semiochemicals have been intensively studied from the viewpoint of ecological relationships with Nearctic tritrophic organisms. However, there are few studies involving interactions with different herbivores on the same host plant in Neotropical systems. The objective of the current study was to investigate the effects of herbivory by two species of stink bugs (Heteroptera: Pentatomidae) with the same feeding habit -Tibraca limbativentris St al and Glyphepomis spinosa Campos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Plant volatiles not only affect the behavior of herbivorous insects but also attract the natural enemies of herbivorous insects, especially the HIPVs [ 4 ]. The HIPVs released by Tibraca limbativentris Stål (Heteroptera: Pentatomidae) and Glyphepomis spinosa Campos et Grazia (Heteroptera: Pentatomidae) feeding on rice are attractive to the natural enemy of the rice pest, Telenomus podisi Ashmead (Hymenoptera: Platygastridae) [ 41 ]. Our results showed that trans-nerolidol, cis-3-hexenyl benzoate, and α-farnesene all appeared after being fed on by A. hygrophila .…”
Section: Discussionmentioning
confidence: 99%
“…Plant volatiles not only affect the behavior of herbivorous insects but also attract the natural enemies of herbivorous insects, especially the HIPVs [ 4 ]. The HIPVs released by Tibraca limbativentris Stål (Heteroptera: Pentatomidae) and Glyphepomis spinosa Campos et Grazia (Heteroptera: Pentatomidae) feeding on rice are attractive to the natural enemy of the rice pest, Telenomus podisi Ashmead (Hymenoptera: Platygastridae) [ 41 ]. Our results showed that trans-nerolidol, cis-3-hexenyl benzoate, and α-farnesene all appeared after being fed on by A. hygrophila .…”
Section: Discussionmentioning
confidence: 99%
“…This focus was given in the work of Togni et al ( 2016 ) who explored the mechanisms involved in the attractiveness of aphidophagous Coccinelids to Coriandrum sativum L. (Apiales: Apieaceae). Also in Brazil, Ulhoa et al ( 2020 ) described that rice plants produce different volatiles in response to damage caused by two species of stink bugs, bringing to the plant protection to conspecific herbivores. However, parasitoids can recognize and respond positively to both stimuli.…”
Section: Conservation Biological Control In Small-scale Agriculture I...mentioning
confidence: 99%
“…Furthermore, rice plants ( Oryza spp.) emit HIPVs and attract T. podisi when subjected to herbivory by two stink bugs, Tibraca limbativentris Stål and Glyphepomis spinosa Campos & Grazia (Melo‐Machado et al, 2014; Ulhoa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%